Output and capital input per capita convergence in Latin America: 1960 - 1995. A preliminary analysis - Elías, Victor (Estudios de Economía, 2016)
This paper studies the convergence in output per capita in 7 Latin American Economies, during the period 1960-1995, breaking it down on its two main determinants: total input and total factor productivity. Total input is in turn broken down in two inputs (labor and capital) and each one of these inputs is separated in its quantity and quality components. The paper presents the convergence of the capital input per capita only. Hence, it presents a partial picture of convergence. However, it gives some useful insights about the economic growth pattern of Latin American economies.